Legal design jako narzędzie umożliwiające osiągnięcie komunikatywności tekstu prawnego - Bieniek, Aleksandra; Lorent, Rafał (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The article discusses the idea of legal design as an approach to legal communication that takes into account the needs of the readers of a normalised legal text and combines linguistic and non-linguistics techniques. It includes examples of legal regulations that refer to the intelligibility and clarity, also discussing the communication challenges that authors of legal texts are faced with. The aim of the article is to explain the term ‘legal design’ whose role as a tool for ensuring communicativeness is becoming more widely recognised by the specialists in the practice and theory of law and linguistics.